2018
DOI: 10.1159/000493226
|View full text |Cite
|
Sign up to set email alerts
|

C. Elegans Fatty Acid Two-Hydroxylase Regulates Intestinal Homeostasis by Affecting Heptadecenoic Acid Production

Abstract: Background/Aims: The hydroxylation of fatty acids at the C-2 position is the first step of fatty acid α-oxidation and generates sphingolipids containing 2-hydroxy fatty acyl moieties. Fatty acid 2-hydroxylation is catalyzed by Fatty acid 2-hydroxylase (FA2H) enzyme. However, the precise roles of FA2H and fatty acid 2-hydroxylation in whole cell homeostasis still remain unclear. Methods: Here we utilize Caenorhabditis elegans as the model and systemically investigate the physiological functions of FATH-1/C25A1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Strikingly, we found that in cgt-1/2/3(−) animals, most intestinal peroxisomes, marked by a peroxisomal matrix protein DAF-22∷GFP(Joo et al, 2009), accumulated in the apical region (Figure 4A-B). The notion that GlcCer deficiency causes apical peroxisomal accumulation is also consistent with a reported observation that apical peroxisomal accumulation was observed with RNAi knockdown of fath-1 (fatty acid 2-hydroxylase)(Li et al, 2018). FATH-1 is involved in biosynthesis of 2-hydroxyl very long chain fatty acid that is present in major GlcCers in C. elegans (Chitwood et al, 1995; Zhang et al, 2011; Zhu et al, 2013)(Figure 1A).…”
Section: Resultssupporting
confidence: 90%
“…Strikingly, we found that in cgt-1/2/3(−) animals, most intestinal peroxisomes, marked by a peroxisomal matrix protein DAF-22∷GFP(Joo et al, 2009), accumulated in the apical region (Figure 4A-B). The notion that GlcCer deficiency causes apical peroxisomal accumulation is also consistent with a reported observation that apical peroxisomal accumulation was observed with RNAi knockdown of fath-1 (fatty acid 2-hydroxylase)(Li et al, 2018). FATH-1 is involved in biosynthesis of 2-hydroxyl very long chain fatty acid that is present in major GlcCers in C. elegans (Chitwood et al, 1995; Zhang et al, 2011; Zhu et al, 2013)(Figure 1A).…”
Section: Resultssupporting
confidence: 90%
“…We next sought to quantify the extent of Rh1 being delivered to the rhabdomeres. Hydroxylated fatty acid metabolism in worms has been shown to influence membrane trafficking mediated by the small GTPases, Rab11 and Rab7 ( Li et al, 2018 ). In Drosophila PRCs, Rab11 colocalizes extensively to newly synthesized Rh1 following its exit from the Golgi and before being deposited in the rhabdomere.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme has been also studied in the yeast Saccharomyces cerevisiae where it was shown to be nonessential for growth (Haak et al, 1997), in the plant Arabidopsis thaliana where it was shown to be involved in the resistance to oxidative stress (Nagano et al, 2012) and in the invertebrate Caenorhabditis elegans in which it was shown to affect intestinal homeostasis, by interfering with heptadecenoic acid production (Li et al, 2018). Alternatively, our experiments demonstrated that growth and morphological parameters were not significantly different between KO and WT strains, suggesting that the gene is nonessential during T. thermophila vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…2‐hydroxy ceramides also regulate the differentiation of various cell types (epidermal keratinocytes, schwan‐noma cells, adipocytes, and megakaryocytic cells) and have been showed to mediate proapoptotic signaling distinct from non‐hydroxy ceramide, as well as the involvement in the regulation of gastric tumor growth (Hama, 2010; Yao et al ., 2019). The enzyme has been also studied in the yeast Saccharomyces cerevisiae where it was shown to be nonessential for growth (Haak et al ., 1997), in the plant Arabidopsis thaliana where it was shown to be involved in the resistance to oxidative stress (Nagano et al ., 2012) and in the invertebrate Caenorhabditis elegans in which it was shown to affect intestinal homeostasis, by interfering with heptadecenoic acid production (Li et al ., 2018). Alternatively, our experiments demonstrated that growth and morphological parameters were not significantly different between KO and WT strains, suggesting that the gene is nonessential during T. thermophila vegetative growth.…”
Section: Discussionmentioning
confidence: 99%